Investigation on Carbon Fiber Based Concrete with Use of Silica Fume (International Journal of Innovative Research in Computer Science & Technology, 2022)
For the construction of civil engineering  works, concrete play main role and a large quantum of  concrete is being utilized. Both coarse aggregate and fine  aggregate which is a major constitute used for making  conventional concrete, has become highly expensive and  also scarce. The investigation was prepared to examine the  harden properties of concrete on the replacement of cement  with silica fumes and fine aggregate with the carbon fibers.  Carbon fibers are thin, tough and adjustable so it has high  tensile strength, low weight, high chemical resistance, low  thermal expansion and have tolerance to high  temperatures. Silica fume has impact on various  characteristics of fresh and cured concrete including  increase in workability and lowering bleeding and  segregation. One nominal mix was prepared and  combination mixes were prepared. M35 grade was used  for mix design. The harden properties of concrete like  compression, split and flexural strength was examined on  replacement of cement with silica fumes and fine  aggregate with carbon fibers. The percentage replacement  was taken as 0%, 5%, 10%, and 20% for silica fumes and  fine aggregate with carbon fibers with 0%, 2.5%, 5 % and  7.5%. The cylindrical specimens, cubes and beams were  prepared for testing after the recommended curing period  of 7 days and 28 days respectively.
Keywords: Carbon fibers; Silica fume; Fiber reinforced concrete; Aggregates; Cement